Sams teach yourself programming with Java in 24 hours - Cadenhead, Rogers (Sams ; Pearson Education [distributor], 2006)
If you have been wanting to learn Java, check out the newly revised fourth edition of the best-seller Sams Teach Yourself Programming with Java in 24 Hours . This step-by-step tutorial will teach you how to create simple Java programs and applets. Comprised of 24 one-hour lessons, this new edition focuses on key programming concepts and essential Java basics, has been improved by dozens of reader comments, and is reorganized to better cover the latest developments in Java. The book's coverage of core Java programming topics has also been expanded. A great starting point for learning Java, this book is also a great primer to reading sams Teach Yourself Java in 21 Days .